2020
DOI: 10.1101/2020.05.19.20103036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical predictors of COVID-19 mortality

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has affected over millions of individuals and caused hundreds of thousands of deaths worldwide. It can be difficult to accurately predict mortality among COVID-19 patients presenting with a spectrum of complications, hindering the prognostication and management of the disease. Methods: We applied machine learning techniques to clinical data from a large cohort of 5,051 COVID-19 patients treated at the Mount Sinai Health System in New York City, the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 28 publications
(25 reference statements)
3
33
0
1
Order By: Relevance
“…Low oxygen saturation (SatO 2 <90%) at admission was also a risk factor for death. This has also been observed in other studies, with small variations in the cutoff point [ 34 , 35 ]. In New York, SatO2 less than 92% was associated with an increased risk of hospital lethality [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…Low oxygen saturation (SatO 2 <90%) at admission was also a risk factor for death. This has also been observed in other studies, with small variations in the cutoff point [ 34 , 35 ]. In New York, SatO2 less than 92% was associated with an increased risk of hospital lethality [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…The flow of studies through our meta-analysis is depicted in Figure 1 . A total of 76 studies with 31,067 patients were eventually included in our study ( 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported risk factors associated with death in patients with COVID-19, although very few propose reliable prediction models, which should be constructed using an adequate sample size and a standardized methodology to avoid significant bias [ 5 , 11 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%